Implementation Website-Based Information Technology to Improve Tourism Destinations of Margacinta Tourism Village in Pangandaran Regency - Andayani, Reni; Nurhastari, Siti; Handayan, Windy; Hamunta, Mohammad Zulfikar; Supriyadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to create a public facility in the form of a website-based portal application that can promote the diversity of tourism and culture in the Margacinta Tourism Village in Pangandaran Regency. The Rapid Application Development (RAD) method will be used as a system development model with requirements planning, RAD Design Workshop and implementation processes. The findings of this study are that the magnitude of the potential of the Margacinta Tourism Village is not matched by measures to promote the attractiveness of tourism, so a website portal application is created that can provide convenience for tourists in searching for tourist information, discovering tourist sites, booking homestays and culinary. It is also hoped that it can be a means to promote Margacinta Tourism Village so that it is better known and can increase visitors optimally in the field of tourism and culture, also can lift the image of Margacinta Tourism Village as one of the tourism and cultural villages that still exist in Indonesia.